Las inteligencias múltiples como estrategias didácticas en el proceso de enseñanza-aprendizaje de los estudiantes con trastornos por déficit de atención e hiperactividad (TDAH) en el sub-nivel elemental de educación general básica de la institución " Academia General Carlos Machado". - Custode, Edison A. (2022)
The objective of the study shown above is to determine multiple intelligences as didactic strategies in the teaching-learning process of students with attention deficit hyperactivity disorder. This research has been developed through surveys to parents and teachers of the educational unit in question, in order to verify the problems presented by the student population that has served as a sample for this study, which has made it possible to determine as a result that parents consider that their sons or daughters do not have learning difficulties and consider hyperactivity as something normal related to age. However, there is a small part of the study that has followed up on their cases and keep the children under treatments. Giving continuity to the problems presented and following the recommendations of the Department of Student Counseling. Therefore, it is important to mention that multiple intelligence is barely known by parents, but it is well known by a group of teachers of the institution. It has allowed to implement strategies for each student to develop their predominant intelligences and potentiate them in the classroom, in addition to stimulating the rest of their multiple intelligences. In conclusion, it is important to mention that the lack of attention of parents towards their sons or daughters can stop their learning process, since when presenting special needs and not being able to treat them, the student will maintain their learning issues.